Smoking-independent DNA methylation markers for lung cancer risk: external validation in a large population-based cohort study - Zhao, Zitong; Bhardwaj, Megha; Fan, Ziwen; Li, Xianzhe; Schrotz-King, Petra; Brenner, Hermann (Cancer science, 2025)
Smoking-associated epigenetic changes have been linked to lung cancer (LC) risk; however, the role of epigenetic alterations independent of smoking is yet to be fully understood. This study aimed to validate 16 previously reported CpG sites that are independent of smoking yet associated with LC risk within a population-based prospective cohort. Using the Infinium Methylation EPIC BeadChip kit or the Infinium HumanMethylation450K BeadChip Assay, DNA methylation (DNAm) in whole blood was assessed in four subsets (n = 736, 1027, 997, and 312) of a population-based cohort from Germany. The DNAm levels of the 16 smoking-independent CpG sites were analyzed. Hazard ratios (HRs) and their 95% confidence intervals (95% CIs) were calculated to assess associations of DNAm at the 16 CpG sites with LC risk, adjusting for multiple covariates, including smoking habits and a smoking-associated DNAm score. Over 17 years of follow-up, a total of 199 LCs were observed. Among the 16 CpGs, cg02211449 showed a negative association with LC risk (HR [95% CI] per SD increase, = 0.70 [0.63-0.78]), while cg11385536 (1.04 [1.01-1.07]), cg09736286 (1.64 [1.10-2.44]), cg19907023 (1.64 [1.01-2.66]), and cg22032485 (1.52 [1.04-2.21]) displayed positive associations with LC risk. Five of the 16 suggested smoking-independent CpGs could be externally validated as predictors of LC risk. Further research should address their potential contribution to enhanced LC risk stratification.